Teen dating and the Value Crisis in Junior and Senior High School Student Education - Nuraini Rahmawati; Nashrul Mu'minin (Universitas Muhammadiyah Malang, 2026)
The normalization of dating practices among junior and senior high school students indicates a shift in adolescents' moral constructions amid the strong influence of popular culture and digital media. This phenomenon raises critical questions regarding the effectiveness of character education based on Islamic values, particularly in internalizing the value of iffah as a principle of self-control and moral integrity. Although character education has become a strategic agenda in the national education system, empirical studies that specifically link adolescents' relational practices with the process of internalizing religious moral values remain relatively limited. Grounded in value internalization theory and moral development theory, this study aims to analyze how adolescents' dating practices reflect the level of iffah value internalization and its implications for character formation. This research employs a qualitative approach with a field study design. Data were collected through in-depth interviews, participatory observation, and document analysis involving students, teachers, and school stakeholders. Analysis was conducted using first-cycle coding techniques and thematic grouping to identify patterns in moral understanding, relational practices, and self-control mechanisms. The findings reveal a gap between normative understanding of iffah and the actualization of behavior in social relations. Most students understand iffah at the cognitive level, yet dating practices are viewed as part of identity formation and adolescents' affective needs. This indicates that the value internalization process has not yet reached a stable stage of moral integration. This study affirms the need for a more transformative, contextual, and collaborative character education model to sustainably strengthen adolescents' moral integrity.